Physical Education in the Era of Artificial Intelligence: The Impact of AI Technology on Enhancing Sports Learning in Schools - Fauzi, Muhammad Sukron; Yantiningsih, Erna; Judijanto, Loso; Prabowo, Iwan Ady (The Future of Education Journal, 2025)
This study aims to examine the impact of Artificial Intelligence (AI) technology in enhancing physical education learning in schools, with a focus on the application of AI in physical education. AI technology has begun to be implemented in various aspects of sports education, ranging from tracking students' physical activities to providing more personalized feedback. The literature review reveals that this technology can assist in monitoring students' performance more thoroughly and offer training programs tailored to individual physical abilities. Several studies reviewed, such as by Smith et al. (2020), show that the use of AI can improve students' physical skills by providing real-time feedback and more accurate training personalization. However, the implementation of AI technology also faces several challenges, such as inadequate technological infrastructure, limited training for teachers, and concerns related to student data privacy. Nonetheless, this study emphasizes that with proper support, AI technology can become a highly effective tool to enhance sports education in schools. Recommendations are made to strengthen teacher training, improve technological infrastructure in schools, and ensure appropriate policies for student data usage.